2020
DOI: 10.1002/jcu.22911
|View full text |Cite
|
Sign up to set email alerts
|

Association between deficient cesarean delivery scar and cesarean scar syndrome

Abstract: Introduction: The aim of our study was to compare long-term morbidity after elective and emergency cesarean delivery (CD). Methods: A prospective cohort study was conducted in 200 women delivered by CD. Ultrasound examinations were performed transvaginally at 6 weeks and 18 months after CD. Clinical data were collected at the time of CD and after 18 months. Results: In the group of 200 women, 29% underwent emergency and 71% elective CD. Then, 6 weeks and 18 months after CD, a severe scar defect was present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…Other studies presented prevalence numbers of 45.6% [8], 56% [10] and 69% [14], however, the results provided by Antila-Långsjö et al and Bij de Vaate et al were collected by means of saline-contrast (SIS) or gel instillation sonohysterography (GIS), respectively. Other authors published much lower prevalence numbers [9,15,16] in TVS-guided examinations, indicating that SIS and GIS may ease the detection of isthmoceles. Important distinctions between the studies are the point in time at which the clinical exams were carried out (e.g.…”
Section: Main Findingsmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies presented prevalence numbers of 45.6% [8], 56% [10] and 69% [14], however, the results provided by Antila-Långsjö et al and Bij de Vaate et al were collected by means of saline-contrast (SIS) or gel instillation sonohysterography (GIS), respectively. Other authors published much lower prevalence numbers [9,15,16] in TVS-guided examinations, indicating that SIS and GIS may ease the detection of isthmoceles. Important distinctions between the studies are the point in time at which the clinical exams were carried out (e.g.…”
Section: Main Findingsmentioning
confidence: 94%
“…Important distinctions between the studies are the point in time at which the clinical exams were carried out (e.g. Dosedla et al chose 6 weeks and 18 months postpartum [16], whereas other authors examined during time periods of 6-12 weeks [11], 6-9 months [14] or 6-12 months postpartum [10] and thus allowed a more heterogeneous time frame) and the individual definitions of a niche. Whilst ours was based on Jordans et al's Delphi study [7] due to their comprehensiveness, Dosedla et al [16] referred to "severe scar defects" based on the thickness of the scar and the adjacent myometrium.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural dynamic contraction of the post-delivery uterus is complicated; post-CS uterine incisions and suturing complicate it even further. Importantly, incomplete closure of the uterine wall is hypothesized to be a surgical factor contributing to CSD pathogenesis, as likely is adhesion formation, which played important role in the biomechanical process and postpartum symptoms related to CSD [22][23][24]. We hypothesize that physical forces and myometrial contraction in the early months postpartum also play an important role in CSD formation.…”
Section: Discussionmentioning
confidence: 95%
“…Osser et al (2010) also showed that a longer labour with a duration of ≥ 5 hours was also associated with larger defects. A recent prospective cohort study of 200 women showed an increased incidence of defects diagnosed by TVUS after emergency CS compared to elective (Dosedla et al, 2020). There appears to be inconsistency with results however, as some other studies have shown an increased risk of niche formation at less cervical dilatation, with presence of labour or emergency CS not being shown as risk factors (Yazicioglu et al, 2006;Hayakawa et al, 2006).…”
Section: Aetiology and Risk Factorsmentioning
confidence: 99%